1986
DOI: 10.1093/cvr/20.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glyceryl trinitrate on peripheral arteries alters left ventricular hydraulic load in man

Abstract: Effects of sublingual glyceryl trinitrate (GTN) were studied in ten patients without heart failure during diagnostic cardiac catheterisation following angiography. GTN caused substantial reduction in peak left ventricular and aortic pressure (19 mmHg) with lesser reduction in mean aortic pressure (9 mmHg) and no change in diastolic aortic pressure. Reduction in stroke volume (by 15%), associated with fall in left ventricular end diastolic pressure (by 4 mmHg) was insufficient to explain the marked (17 mmHg - 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
120
1
5

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(136 citation statements)
references
References 0 publications
10
120
1
5
Order By: Relevance
“…Both effects would contribute to reducing the propagative properties of arterial wave velocities in the aorta. 37,38 In our model, the AoStiff index is a variable integrating two components: the local resistance of the aorta to the flow (that is, the turbulences and the mean shear stress) and the distensibility of the aortic wall, which could vary independently. With GTN administration, both components may counterbalance each other, leading to an apparently unchanged AoStiff.…”
Section: Discussionmentioning
confidence: 99%
“…Both effects would contribute to reducing the propagative properties of arterial wave velocities in the aorta. 37,38 In our model, the AoStiff index is a variable integrating two components: the local resistance of the aorta to the flow (that is, the turbulences and the mean shear stress) and the distensibility of the aortic wall, which could vary independently. With GTN administration, both components may counterbalance each other, leading to an apparently unchanged AoStiff.…”
Section: Discussionmentioning
confidence: 99%
“…Vasoconstriction has little effect on wave reflection from the peripheral vascular bed, probably because wave reflection is already high under control circumstances as a result of high resting arteriolar tone, whereas vasodilation causes profound reduction in wave reflection. Effects of vasodilation on ascending aortic pressure wave contour have been studied by Takazawa, 22 Yaginuma et al, 25 and Fitchett et al 29 All have shown marked reduction in the amplitude of the late systolic pressure peak in the ascending aorta of human adults with nitroglycerin. Yaginuma et al 25 and Fitchett et al 29 have measured ascending aortic impedance as well and have confirmed that this change in pressure was attributable to reduction of wave reflection from peripheral sites.…”
Section: Effects Of Vasodilator Agents On Arterial Wave Reflection Anmentioning
confidence: 99%
“…Effects of vasodilation on ascending aortic pressure wave contour have been studied by Takazawa, 22 Yaginuma et al, 25 and Fitchett et al 29 All have shown marked reduction in the amplitude of the late systolic pressure peak in the ascending aorta of human adults with nitroglycerin. Yaginuma et al 25 and Fitchett et al 29 have measured ascending aortic impedance as well and have confirmed that this change in pressure was attributable to reduction of wave reflection from peripheral sites. This has recently been confirmed in dogs by Latson et al 30 Because the effect of nitroglycerin was seen without reduction in peripheral resistance, all investigators attributed this phenomenon to dilation of small conduit arteries.…”
Section: Effects Of Vasodilator Agents On Arterial Wave Reflection Anmentioning
confidence: 99%
“…3,13 For example, nitroglycerin administration produces marked changes in the pressure pulse waveshape, which can be dissociated from a change in total peripheral resistance or the pulse transit time measured by aortic pulse wave velocity. 14,15 The effects are explained by changes in the mechanical properties of peripheral muscular arteries that result in improved impedance matching and attenuation of wave reflection in response to nitroglycerin. Direct ultrasonic techniques employed to assess local wall properties of peripheral muscular arteries indicate that arterial compliance (a property that depends on arterial geometry and intrinsic vessel wall properties) improves consistently, whereas distensibility (an intrinsic property of the arterial wall materials) does not necessarily change in response to nitroglycerin administration.…”
mentioning
confidence: 99%